The practice and characteristics of significant mantras at the Vajrakilaya Drupchen ritual in Malaysia - Wong, Josephine Eng Jun; Loo, Fung Chiat (American Research Institute for Policy Development, 2018)
This paper reports an observation on the chants used in Dudjom New Treasure Buddhist Society Ipoh, Malaysia. Vajrakilaya Drupchen is performed with the main intention of benefiting the well-being of the world community as a whole for world peace and harmony. The purpose is to provide better understanding of one of the most important Buddhist ceremonies, Vajrakilaya Drupchen (the Great Accomplishment Ritual), through the musical practices of the ritual ceremony. As most of the mantras were orally transmitted, this article looks into a root mantra and two significant mantras of Vajrakilaya ritual. These mantras were transcribed in which the characteristics and musical element were analysed and discussed. Attention will be given to the structure, motivic ideas and pitch of chants. The characteristics of these mantras in comparison with other schools in the same lineage will also be highlighted.